Assessment of the Effectiveness of Biophysical Soil and Water Conservation Structures: A Case Study of Offa Woreda, Wolaita Zone, Ethiopia - Elias Bojago; Marisennayya Senapathy; Innocent Ngare; Tsegeye Bojago Dado (Applied and Environmental Soil Science)
Soil erosion is a serious environmental and natural resource issue in Ethiopia, posing a significant threat to agricultural productivity and being one of the principal drivers of land degradation and soil fertility reduction. Evaluating the biophysical soil and water conservation structures’ effectiveness in Offa Woreda, Wolaita Zone, was the focus of the study. Purposive sampling was used to select the three kebeles that make up this watershed. W/Dekeya, Wareza, and Yakima are the three watersheds chosen for the selected study area. To meet the objective of this study, 504, 325, and 442 family heads were sampled. They comprised the overall 17% (227) of the study participants that were selected. Those who knew how to conserve soil and water, causes of degradation, and sensitive areas of their own plots of land in the study area received preference. The lack of capital, a short stretch of land, and various socioeconomic and physical conditions impeded the use of soil and water conservation systems. As a result, farmers have a reasonable position of the current biophysical soil and water conservation systems. Farmers in the study communities are aware of some traditional soil and water conservation practices as a measure to protect and restore the fertility and productivity of their farmlands. Community participation in encouraging farmers to participate in soil and water conservation practices is critical to resolving the issue of cutting-edge poverty, food insecurity, and environmental deterioration. From the study, we recommend that the government implements specific coverage and techniques as well as corrective intervention from nongovernmental organizations.